Perception of training in hepatopancreatobiliary surgery among general surgery residents in the Americas. Issue 12 (December 2016) - Sheikh, Mohd Raashid; Osman, Houssam; Butt, Muhammad Umar; Jeyarajah, Dhiresh Rohan
Abstract: Background: Hepatopancreatobiliary (HPB) surgery experience during residencyin the Americas is limited. Residents interested in HPB surgery have different options available for further training. This study evaluated training in HPB surgery received during general surgery (GS) residency, and sought to determine the perception of fellowship training in HPB surgery. Methods: An anonymous survey was distributed to all 259 GS residency programs in the United States. Questions evaluated demographics, program structure, overall training & HPB experience in particular during residency, plans for fellowship training and understanding of training in HPB surgery. Results: Of the 340 respondents, 162 (48%) were from university programs, 145 (43%) from community hospitals and 48 (14%) from independent medical centers. 117 (34%) were residents in postgraduate year 4 or 5 (PGY4/PGY5). 275 (81%) respondents were planning to pursue fellowship training after finishing residency. Three quarters of all respondents did not feel comfortable about performing liver, biliary and pancreatic procedures. Fellowships accredited by the Americas Hepato-Pancreatico-Biliary Association (AHPBA) are the most common pathway considered by residents for HPB training. Conclusions: GS residents are not comfortable in considering performing complex HPB cases on completion of residency training. GS residents consider AHPBA accredited fellowships to be more suitable for advanced training in HPB surgery.